2019
DOI: 10.1080/02656736.2019.1641634
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictors of incisional hernia after cytoreductive surgery and hyperthermic intraperitoneal chemotherapy

Abstract: Background and objectives: The incidence of incisional hernia (IH) after cytoreductive surgery plus hyperthermic intraperitoneal chemotherapy (CRS/HIPEC) is largely unknown. Methods: We conducted a retrospective study to identify patients who underwent CRS/HIPEC from 2001 to 2016. Patients were followed postoperatively for a minimum of two years. The primary outcome was the occurrence of an IH identified either on CT scan or physical examination. Univariate and multivariable logistic regression models were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 22 publications
0
14
1
Order By: Relevance
“…Finally, whilst chemotherapy, which is common in HPB procedures such as hepatectomies for metastases and pancreatectomies for pancreatic cancer, was only identified as a significant risk factor by Nilsson et al [36], Arslan et al [35] also observed a non-significant trend between IH and postoperative chemotherapy. Wound healing impairment secondary to systemic or intraperitoneal chemotherapy have been reported as a risk factor for IH formation [44]; however, there was not a clear association seen in our review. More studies exclusively analysing the incidence of IH after liver resections for colorectal metastases should be designed to confirm the association of chemotherapy found by Nilsson et al [36].…”
Section: Discussioncontrasting
confidence: 83%
“…Finally, whilst chemotherapy, which is common in HPB procedures such as hepatectomies for metastases and pancreatectomies for pancreatic cancer, was only identified as a significant risk factor by Nilsson et al [36], Arslan et al [35] also observed a non-significant trend between IH and postoperative chemotherapy. Wound healing impairment secondary to systemic or intraperitoneal chemotherapy have been reported as a risk factor for IH formation [44]; however, there was not a clear association seen in our review. More studies exclusively analysing the incidence of IH after liver resections for colorectal metastases should be designed to confirm the association of chemotherapy found by Nilsson et al [36].…”
Section: Discussioncontrasting
confidence: 83%
“…Nevertheless, previous reports on CRS-HIPEC showed no additional risk for IH after this procedure, with IH rates of less than 10% in most of them. [5][6][7][8] Based on our clinical experience, the rates of IH after CRS-HIPEC were much higher than previously reported. The aim of this study was to evaluate the rate of IH after CRS-HIPEC and its risk factors.…”
Section: Introductionmentioning
confidence: 50%
“…Cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (CRS‐HIPEC) is potentially prone to hernias because it is a Xiphoid to pubis incision performed on patients who have undergone previous abdominal surgeries with the addition of chemotherapy and its related adverse effects (2). Nevertheless, previous reports on CRS‐HIPEC showed no additional risk for IH after this procedure, with IH rates of less than 10% in most of them 5–8 …”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…In our study, BMI was not deemed an influencing factor of IH. However, many studies have shown that BMI, especially BMI > 30 (obesity), is a risk factor for IH [ 33 , 34 ]. Obesity is likely to increase intra-abdominal pressure by putting mechanical stress on the abdominal incision, thus predisposing the occurrence of a hernia.…”
Section: Discussionmentioning
confidence: 99%